Impact of plyometric training on skill component in young volleyball players - Shehu, Aida; Gorenca, Altin; Qefalia, Dean (Edelweiss Applied Science and Technology, 2026)
This study aimed to examine the effectiveness of a 12-week plyometric training program in improving agility in young male volleyball players. Methods: 42 volleyball players (mean age = 15 ± 1.3 years) from Tirana, Albania, with five years of experience and training four times a week for 90 minutes, participated in the study. Participants were randomly assigned to an experimental group (EG, n = 21) and a control group (CG, n = 21). EG completed a 12-week plyometric program with seven exercises, three times a week for 20 minutes after regular ball training. Groups were assessed before and after the intervention on anthropometric measures (body height, body weight, BMI) and agility tests (T-Test and Conical Agility Training). Descriptive statistics and ANOVA (p < .05) were used to analyze the data. Results: Significant improvements were observed in EG. T-Test performance increased from 14.11 s to 15.42 s, and Conical Agility Training improved from 13.43 s to 11.25 s, CG showed minimal changes. Conclusions: A 12-week plyometric program effectively and rapidly increases agility in young male volleyball players. These findings highlight the importance of incorporating structured plyometric exercises into regular training sessions to improve multidirectional and lateral agility.